Secondhand smoke is associated with peptic ulcer disease and gastroesophageal reflux disease in non-smokers in a large Taiwanese population study - Yen, Pei-Chi; Geng, Jiun-Hung; Wu, Pei-Yu; Huang, Jiun-Chi; Hu, Huang-Ming; Kuo, Chao-Hung; Chen, Szu-Chia (Frontiers in Public Health, 2024)
Background: Active smokers are known to be at an increased risk of both gastroesophageal reflux disease (GERD) and peptic ulcer disease (PUD), however the role of passive smoking remains unclear. In this study, we aimed to examine whether secondhand smoke (SHS) is associated with PUD and GERD.In this population-based study, we conducted a large-scale analysis with 88,297 never-smokers (male: 18,595; female: 69,702; mean age 50.1 ± 11.0 years) from the Taiwan Biobank. The exposure group was comprised of those who had been exposed to SHS, and the no exposure group as those without SHS exposure.According to the frequency of exposure, we further divided the participants into "no exposure", "< 1 hour per week", and "≥ 1 hour per week" groups. A cutoff point of 1 hour per week was chosen according to the median exposure time in our participants.Associations between SHS and SHS frequency with PUD and GERD were assessed.Results: Of the 88,297 enrolled participants, 11,909 (13.5%) had PUD and 76,388 (86.5%) did not. In addition, 11,758 (13.3%) had GERD and 76,539 (86.7%) did not.Multivariable analysis showed a significant association between SHS with PUD (odds ratio [OR] = 1.166; 95% confidence interval [CI] = 1.084-1.254; p < 0.001), and GERD (OR = 1.131; 95% CI = 1.053-1.216; p = 0.001). Furthermore, those exposed to SHS ≥ 1 hour per week (vs. no exposure) were associated with higher risks of PUD (OR = 1.232; 95% CI = 1.121-1.355; p < 0.001) and GERD (OR = 1.200; 95% CI = 1.093-1.319; p < 0.001).SHS was significantly associated with PUD and GERD. Furthermore, exposure to SHS ≥ 1 hour per week (vs. no exposure) was associated with a 1.23-fold higher risk of PUD and 1.20-fold higher risk of GERD. This study represents the largest population-based investigation to explore the association between SHS with PUD and GERD in Taiwanese never-smokers. 4